1984
DOI: 10.1247/csf.9.235
|View full text |Cite
|
Sign up to set email alerts
|

Electric characteristics of the vacuolar membrane of Chara in relation to pH regulation.

Abstract: ABSTRACT. The vacuolar pH of Chara internodal cells was modified by vacuolar perfusion, and changes in membrane potential and membrane resistance of the tonoplast in response to the vacuolar pH (pHv) change were studied by anesthetizing the cell with 110 mM KCl in the external medium. Under this condition the responses of the vacuolar potential (Ev o) and resistance (Rvo) are assumed to reflect the responses of the tonoplast. E, o showed scarcely any sensitivity to the pHv when the KCl concentration of the vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2

Year Published

1987
1987
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 25 publications
0
8
2
Order By: Relevance
“…They added 50 mM propionic acid (pH^, 6.5) and found pH^ to be rapidly decreased by about 0.3 pH units; but, in contrast to cytoplasmic pH, there was no significant recovery. However, these findings are by no means contradictory to the observations of Moriyasu et al (1984a), because acidifying cellular compartments with externally added weak acids is an altogether different experiment than perfusion and subsequent exchange of the cell sap. Weak acids have the tendency to clamp internal pH, unless active mechanisms prevent it.…”
Section: Regulation Of Vacuolar Phcontrasting
confidence: 61%
See 1 more Smart Citation
“…They added 50 mM propionic acid (pH^, 6.5) and found pH^ to be rapidly decreased by about 0.3 pH units; but, in contrast to cytoplasmic pH, there was no significant recovery. However, these findings are by no means contradictory to the observations of Moriyasu et al (1984a), because acidifying cellular compartments with externally added weak acids is an altogether different experiment than perfusion and subsequent exchange of the cell sap. Weak acids have the tendency to clamp internal pH, unless active mechanisms prevent it.…”
Section: Regulation Of Vacuolar Phcontrasting
confidence: 61%
“…Using antimony electrodes, Moriyasu et al (1984a) demonstrated pH^, regulation in perfused internodal cells of Chara australis. After replacing the natural ceil sap (pH 5) by artificial sap of pH 6, the pH^, gradually returned to 5, a process inhibited by DCCD.…”
Section: Regulation Of Vacuolar Phmentioning
confidence: 99%
“…The Plexiglas tube was 175 mm long. Recording of the action potential was similar to that described previously (Moriyasu et al, 1984;Clint and MacRobbie, 1987). Briefly, the Plexiglas support compartment was filled with 100 mM KCl.…”
Section: Methodsmentioning
confidence: 99%
“…The technique of vacuolar perfusion has contributed further to studies on the mechanism of excitation of the tonoplast , measurement of the motive force of cytoplasmic streaming (Tazawa 1968), amino acid metabolism (Sakano and Tazawa 1985), pH regulation of the vacuole (Moriyasu et al 1984a(Moriyasu et al , 1984b and the proteases in the vacuolar sap (Moriyasu and Tazawa 1986;Moriyasu et al 1987).…”
Section: Intracellular Perfusion In Characean Cellsmentioning
confidence: 99%